Phase II study evaluating consolidation whole abdominal intensity-modulated radiotherapy (IMRT) in patients with advanced ovarian cancer stage FIGO III - the OVAR-IMRT-02 study - Rochet, Nathalie; Kieser, Meinhard; Sterzing, Florian; Krause, Sonja; Lindel, Katja; Harms, Wolfgang; Eichbaum, Michael H. R.; Schneeweiss, Andreas; Sohn, Christof; Debus, Jürgen (BMC cancer, 2011)
The prognosis for patients with advanced FIGO stage III epithelial ovarian cancer remains poor despite the aggressive standard treatment, consisting of maximal cytoreductive surgery and platinum-based chemotherapy. The median time to recurrence is less than 2 years, with a 5-years survival rate of -20-25%. Recurrences of the disease occur mostly intraperitoneally.
Gesehen am 19.09.2022